EPIDERMAL GROWTH FACTOR RECEPTOR OVEREXPRESSION IN TRIPLE NEGATIVE BREAST CANCER - Safdar, Ayesha; Khan, Maria; Mahmood, Raazia; Javaid, Faryal; Sajjad, Ayesha; Khattak, Dr Maria Tasneem; Muhammad khan, Iqbal (Journal of Postgraduate Medical Institute, 2024)
Objective: To observe the frequency of EGFR overexpression and its correlation with clinicopathological parameters in patients diagnosed with triple negative breast carcinoma. Methodology: This Cross-sectional study was conducted at Rehman Medical Institute from June 2022 to June 2023. Biopsy specimen of 41 female patients diagnosed with triple negative breast carcinoma (TNBC) were received in histopathology department. Specimen underwent eosin and hematoxylin staining and immunohistochemistry analysis. Demographic characteristics and histopathological parameters were recorded. Results: Mean age of the participants was 46.27 ± 3.75 years. Axillary metastasis was observed in 24 (58.5%) patients while perinodal extension was observed in 05 (12.2%) patients. Immunohistochemistry analysis revealed 23 (56.1%) EGFR positive specimens while 18 (43.9%) specimens were EGFR negative. Out of 23 patients with axillary metastasis the frequency of EGFR positive carcinomas was 17 (73.9%) which was significantly greater than 06 (26.1%) patients exhibiting negative EGFR expression. Frequency of EGFR positive expression was significantly increased with higher grade and stage of the tumor (p-value <0.05). Conclusion: EGFR overexpression in Triple negative breast carcinoma is associated with poor clinicopathological indicators which leads to poor prognosis.